Patočka i Masaryk - Zumr, Josef (Folia Philosophica, 2018)
The aim of the paper is to analyse relation between Jan Patočka and Tomáš G.Masaryk. The former was referring to the latter’s concepts throughout his work, inmost cases from the perspective of Edmund Husserl’s phenomenology. According toPatočka, both in Masaryk and Husserl the most important symptom of crisis is thepositivist hypostising of the scientific method and the loss of religion. The commonstarting point of both theories was the thesis according to which Europe is goingthrough a spiritual crisis which arises from subjectivism. The difference betweenthem, however, was in the concepts of the ways to resolve the crisis. According toMasaryk, the solution is to be found in restoration of religion, whereas Husserl seesit in transcendental phenomenology. Patočka was wrong when he stressed how muchout of date were Masaryk’s views. For they might be taken as topical in their moraland religious aspects, value of which was proved during the hard times for Czechand Slovak nations.